Strength prediction of Class G oilwell cement during early ages by electrical conductivity - Sonny Irawan, Sonny (Springer-Verlag, 2013)
The compressive strength of oilwell cement plays an important role in securing the long-term integrity of wellbore. The cement’s strength development is experimentally difficult to perform once the cement has been displaced into the wellbore. Failure to monitor its development especially during early hydration may lead to secondary cementing operation or in the worst case may damage the well. This paper proposes an empirical equation for strength prediction of Class G oilwell cement using electrical conductivity at elevated pressure up to 3,000 psi and temperature up to 65 C during the first 24 h of hydration. The study used both porosity–strength correlations and strength–electrical properties relationship to produce predictive equation for strength of oilwell cement. The proposed equation was experimentally compared to cement samples with different water–cement ratios and curing conditions to validate the result. A good agreement is achieved between the proposed equation and the measured data. Furthermore, the strength up to 50 days can be predicted by the proposed equation